Ergonomic Intervention in Malaysian Small and Medium Industries - Isa, Halim (2007)
Ergonomic interventions have been carried out in small and medium industries in Malaysia. Sheet metal stamping industries' workers are exposed to higher body vibrations and they stand and work throughout their shifts. Ergonomic interventions are made in two small industries involved with sheet metal stamping works. A Larson Davis HVM 100 (Human Vibration Meter) was used to measure the whole body vibration of a operator working on a 65 Tons stamping machine. A 3-axis pad with built in accelerometer was placed under the feet of the worker and whole body vibration was measured based on ISO 2631-1. Thick rubber platforms interposed between the worker and the floor of the industry absorb the vibration and removes the discomfort experienced by the worker. It was found that the magnitude of whole body acceleration reduced about 78 percent with the inception of the rubber anti-vibration pad under the worker's feet. Ergonomic interventions were made in another metal stamping company, which uses a lot of manual materials activities while producing their products. The production shop floor consists of stamping machines having capacities ranging from 25 tons to 250 tons. Ergonomic redesign of workplaces with suitable lift tables and alternate sit/stand postures are found to remove the discomfort from workers to a greater extent.